The relationship between learning motivation and policy support perception among government-funded normal university students in ethnic minority institutions based on group dynamics and its application in educational management - Wang Wei; Aida Hanim A. Hamid; Bity Salwana Alias (Environment and Social Psychology, 2026)
This study examines the relationship between learning motivation and policy support perception among government-funded normal university students in ethnic minority institutions. The research is grounded in group dynamics theory. We adopted an embedded mixed-method design. The participants included 1,087 students from four ethnic minority universities in western China. Data collection involved questionnaires, in-depth interviews, and multilevel statistical analysis. The findings reveal several patterns. First, group norms, group identity, and group cohesion exerted significant influence on learning motivation. They accounted for 18.5%, 23.2%, and 21.4% of motivation variance respectively. Second, policy support perception showed a significant positive correlation with learning motivation (r=0.52, p<0.001). Different policy dimensions had differentiated effects on different motivation types. Third, teacher professional identity played a partial mediating role in this relationship. The mediating effect represented 34.6% of the total effect. Fourth, group cohesion significantly moderated the impact of policy perception on learning motivation (γ=0.15, p<0.01). The policy effect in high-cohesion classes was 1.94 times that in low-cohesion classes. Fifth, the integrated structural equation model explained 58.7% of the variance in learning motivation. The study unveils the psychological transformation mechanism of "policy support → professional identity → learning motivation". It also demonstrates the contextual moderating role of group dynamics elements. These findings provide theoretical foundation and practical guidance for educational management in ethnic minority institutions and the cultivation of government-funded normal university students.